FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGELOLAAN SAMPAH RUMAH TANGGA - Alprindo Sembiring (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
The problems that is examined in this study are factors related to household waste management. The purpose of this study was to determine the factors associated with household waste management. The type of research was analytical research with cross sectional design. The independent variable were income, knowledge, availability of facilities and infrastructure, and socialization. The total population in this study was 4.216 inhabitants. Samples taken as many as 98 people. The sampling technique used stratified random sampling. Data analysis used Chi-square test with a = 0.05. From the results of the study, it is found that the respondents income about household waste management earning <DMW (Rp3,003,922) was 56.1%, bad knowledge was 60.2%, availability of facilities and infrastructure was not available by 56.1%, good socialization by 51 0%. Statistical test results showed that income and household waste management p = 0.009, the level of knowledge and household waste management p = 0.034, the availability of facilities and infrastructure and household waste management p = 0.034, socialization and management household waste obtained p = 0.556. The conclusion of this study that there was relationship between income, knowledge, availability of facilities and infrastructure with household waste management, while socialization has no relationship with household waste management. Suggestions are recommended for people who live in the village to increase knowledge about good household waste management.